The outsiders. - Scott-Parker, Susan; Holmstrom, Radhika (New Statesman & Society, 1995)
There is an undeniable need in Britain for a credible legislative framework to deal with disabled people and employment. Both disabled people and employers are frustrated with the present situation. The former say that they never even get to the interview stage, and the majority of the latter say that no disabled people apply to them for jobs. The Employers' Forum on Disability was established in 1986 to facilitate the development of a fresh approach to the relationship between employers and disabled people. Only 30 percent of disabled people are in full-time employment, and this wastes a significant pool of talent that employers cannot afford to ignore. The forum is pleased that the government's Disability Discrimination Bill acknowledges the principle that disabled people should have antidiscrimination legislation in employment as well as in relation to access to goods and services, but it is concerned about the practical applicability of the bill. Problems with the proposed legislation are discussed.